Enzymatically regulated demineralisation of pathological bone using sodium hexametaphosphate. Issue 21 (6th May 2016) - Eisenstein, Neil; Williams, Richard; Cox, Sophie; Stapley, Sarah; Grover, Liam
Abstract : Human heterotopic ossification before (A) and after (B) incubation in hexametaphosphate. Abstract : The pathological formation of bone in soft tissue can result in significant disability, prevent prosthetic limbs from fitting, and limit joint movement. A range of conditions exist, which are characterised by this local tissue ossification. The awareness of one such condition, heterotopic ossification, has increased recently due to the extraordinarily high incidence of the condition in military amputees (64.6%). Although the process of formation is biologically mediated through a massive inflammatory response, there is currently no adequate treatment or prophylaxis for the condition. This study investigates the use of hexametaphosphate (HMP) as a demineralising agent for the treatment of pathological ossification. Other demineralising agents exist but their application is limited due to unwanted effects on biological processes such as blood clotting and an inability to control their activity. This study demonstrates, for the first time, that the demineralising effect of HMP can be modified by local pH and is controlled through the activity of alkaline phosphatase, an enzyme that is found throughout the body. HMP was shown, using micro computed tomography, to cause large scale demineralisation of samples of pathological bone and was able to inhibit hydroxyapatite precipitation in a supersaturated solution. Stiffness and maximum force to failure of rat tibiae incubated in HMP were 49% ( p = 0.001) and 41% ( p = 0.03) lower, respectively, than controls. In contrast, no significant difference was observed in yield force, demonstrating specificity of action of HMP against hydroxyapatite, with no unwanted effect on collagen. Contrary to established understanding of the mechanism of its dissolution of calcium phosphate salts, micro X-ray fluorescence measurements of the hydroxyapatite surfaces suggested that the demineralising effect was mediated in the solution rather than surface binding of HMP. These findings suggest that HMP is effective at dissolving hydroxyapatite and, as such, is a promising a candidate for the treatment of a range of pathological ossifications.